Enhanced stratospheric intrusion at Lulin Mountain, Taiwan inferred from beryllium-7 activity. (1st January 2022) - Huang, Shengyi; Huang, Pin-Ru; Newman, Sally; Li, King-Fai; Lin, Yu-Chi; Huh, Chih-An; Lin, Neng-Huei; Hsu, Shih-Chieh; Liang, Mao-Chang
Abstract: Beryllium-7 ( 7 Be), produced by the interaction of cosmic radiation with atoms and molecules primarily in the upper troposphere and lower stratosphere, provides a useful tracer of cross-tropopause transport and vertical mixing in the troposphere. In the western Pacific subtropical region, the interaction of the subtropical jet stream with monsoon systems potentially enhances the transport. Here, we report one year of 7 Be measurements at daily resolution during 2010, at Mt. Lulin (2862 m above mean sea level; NOAA code: LLN), along with other gaseous compounds such as O3 and CO and meteorological information, to assess processes that affect the variability of 7 Be. The 7 Be concentrations are of the order 1 mBq/m 3 or less. The 7 Be activity is generally low during summer, largely due to precipitation and unfavorable conditions of atmospheric dynamics (i.e., prevalence of upward motion), but it is occasionally high because of the influence of typhoons. In winter and spring, stratospheric effects observed at the surface were frequent and significant, thereby directly affecting the strength of stratospheric effects on the troposphere, such as the tropospheric oxidation capacity. The effects of the stratospheric intrusions are seen by negative and positive correlations of 7 Be with relative humidity and concentration of O3, respectively. The stratospheric effect is further supported by the presence of downwelling transport in this region in the European Centre for Medium-Range Weather Forecasts-Atmospheric Composition Reanalysis Version 4 CO, O3, and relative humidity data. Highlights: We report one-year of daily 7 Be concentrations at Lulin Mountain, Taiwan. Located in an Asian minimum region, 7 Be at Lulin is low at about 1 mBq/m 3 or less. Frequent, sporadic, and sharp increases in 7 Be are linked to stratospheric intrusions. The subtropical jet stream and typhoons help induce the intrusions.